PENGARUH KEBIJAKAN DIVIDEN DAN VARIABEL LAINNYA TERHADAP NILAI PERUSAHAAN - Birgita, Evelyn; Almalita, Yuliani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to obtain the empirical evidence about the influence of profitability, leverage, liquidity, dividend policy, firm size, managerial ownership, institutional ownership, and firm age on firm value. The population in this study were manufacture companies listed in the Indonesia Stock Exchange from 2019-2021. Samples were obtained through purposive sampling method resulting in 123 data samples. This study was used multiple regression method to evaluate the hypothesis. The results of this study indicated that profitability have a positive effect on firm value because a high profitability gave an indication of good corporate prospects that interest investor to invest, leverage have a positive effect on firm value because the public believe that corporates were able and credible to pay for their debts, dividend policy have a positive effect on firm value because indicated corporate have a good going concern, and firm age have a positive effect on firm value because corporates with longer age gain public trust to invest because they were sustainable in all economic conditions. Meanwhile liquidity, firm size, managerial ownership, institutional ownership have not affect on firm value.